IMPLEMENTASI PENGELOLAAN KELAS DALAM PEMBELAJARAN TAJWID PADA PENDIDIKAN NONFORMAL: STUDI PADA KEGIATAN PENGAJIAN MALAM - Rahmasari, Adinda; Astuti Darmiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study describes classroom management in Tajweed learning within evening religious study activities as a form of nonformal education. The problem arises from heterogeneous learners, limited learning time, and learners’ difficulty in applying Tajweed rules when reading the Qur’an. This qualitative case study involved one instructor and approximately 25 learners from elementary to senior high school levels. Data were collected through observation, interviews, and documentation, then analyzed through reduction, display, and conclusion drawing. The findings show that classroom management was implemented through opening murajaah, peer tutoring, gradual material delivery, demonstration, questioning, direct reinforcement, and repeated evaluation. Supporting factors included the instructor’s experience, available facilities, peer assistance, and positive teacher-student interaction. Obstacles included differences in age and ability, limited time, and weak awareness of Tajweed practice. Proper classroom management helped create active, orderly, and meaningful Tajweed learning.